Оптимізація конструктивних та технологічних параметрів борони з гвинтовими робочими органами - Клендій, Микола Богданович; Драган, Андрій Петрович; Klendii, Mykola; Drahan, Andrii (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті досліджено процес оптимізації конструктивних і технологічних параметрів борони з гвинтовими робочими органами. Обґрунтовано використання узагальненого критерію ефективності та побудовано регресійну модель, що описує залежність якості заробляння рослинних решток від основних факторів: глибини обробітку, кута атаки та кроку гвинтового органу. Експериментальні дослідження дозволили встановити закономірності впливу зазначених параметрів та визначити їх оптимальні значення. Доведено, що найбільший вплив має глибина обробітку та кут атаки, тоді як крок гвинтового органу є менш значущим фактором. /// EN: The article addresses the problem of optimizing the design and technological parameters of a harrow with screw-type working bodies intended for efficient soil tillage and incorporation of crop residues. The expediency of using a generalized efficiency criterion, which takes into account labor intensity, energy consumption, and material consumption, is substantiated. To assess the quality of the technological operation, the indicator of the percentage of the field surface area with complete incorporation of plant residues is used. Experimental studies were carried out under field conditions using a developed harrow design. The influence of the main factors – tillage depth, angle of attack of the working body, and pitch of the screw helix – on the efficiency of the technological process was determined. Based on the mathematical design of experiments, a regression model in the form of a quadratic polynomial was obtained, which adequately describes the dependence of the quality indicator on the studied parameters within the specified variation ranges. It was established that the greatest influence on the quality of incorporation of plant residues is exerted by the tillage depth, as well as the angle of attack of the screw working bodies. An increase in tillage depth and angle of attack leads to an increase in the proportion of the field area with fully incorporated residues, whereas an increase in the screw pitch results in a slight decrease in this indicator. Response surface plots were obtained, reflecting the interaction of factors and enabling the determination of rational operating parameters of the harrow. Based on the research results, optimal parameter ranges were established, ensuring maximum tillage quality.
Optimization of structural and technological parameters of a harrow with screw working bodies
Keywords: пожнивні залишки; кут атаки; борона; гвинтовий робочий орган; ґрунтообробна машина; глибина обробітку ґрунту; crop residues; angle of attack; harrow; screw working body; tillage machine; tillage depth